Poly[ADP-ribose] polymerase-1 expression is related to cold ischemia, acute tubular necrosis, and delayed renal function in kidney transplantation. - Francisco O'Valle; Raimundo G M Del Moral; María del Carmén Benítez; David Martín-Oliva; Mercedes Gómez-Morales; David Aguilar; José Aneiros-Fernández; Pedro Hernández-Cortés; Antonio Osuna; Francesc Moreso; Daniel Serón; Francisco J Oliver; et al. (PLoS ONE, 2009)
UNLABELLED:Cold ischemia time especially impacts on outcomes of expanded-criteria donor (ECD) transplantation. Ischemia-reperfusion (IR) injury produces excessive poly[ADP-Ribose] Polymerase-1 (PARP-1) activation. The present study explored the hypothesis that increased tubular expression of PARP-1 contributes to delayed renal function in suboptimal ECD kidney allografts and in non-ECD allografts that develop posttransplant acute tubular necrosis (ATN). MATERIALS AND METHODS:Nuclear PARP-1 immunohistochemical expression was studied in 326 paraffin-embedded renal allograft biopsies (193 with different degrees of ATN and 133 controls) and in murine Parp-1 knockout model of IR injury. RESULTS:PARP-1 expression showed a significant relationship with cold ischemia time (r coefficient = 0.603), time to effective diuresis (r = 0.770), serum creatinine levels at biopsy (r = 0.649), and degree of ATN (r = 0.810) (p = 0.001, Pearson test). In the murine IR model, western blot showed an increase in PARP-1 that was blocked by Parp-1 inhibitor. Immunohistochemical study of PARP-1 in kidney allograft biopsies would allow early detection of possible delayed renal function, and the administration of PARP-1 inhibitors may offer a therapeutic option to reduce damage from IR in donor kidneys by preventing or minimizing ATN. In summary, these results suggest a pivotal role for PARP-1 in the ATN of renal transplantation. We propose the immunohistochemical assessment of PARP-1 in kidney allograft biopsies for early detection of a possible delayed renal function.